Respuesta :

Answer:

[tex]a_0 = -8[/tex]

[tex]a_1=-6[/tex]

[tex]x^2 +y^2 -8x - 6y = 0[/tex]

Step-by-step explanation:

The equation of the circle has the following form

[tex]x^2 + y^2 + a_0x + a_1y=0[/tex]

The equation of the circle has the following form

We know that the circle goes through the following points

(1, 7)

(8, 6)

(7, -1).

Then we substitute the values of x and y in the equation

For (1, 7)

[tex](1)^2 + (7)^2 + a_0(1) + a_1(7)=0[/tex]

[tex]1 + 49 + a_0 + 7a_1=0[/tex]

[tex]a_0 + 7a_1=-50[/tex]    (1)

For  (8, 6)

[tex](8)^2 + (6)^2 + a_0(8) + a_1(6)=0[/tex]

[tex]64 + 36 + 8a_0 + 6a_1=0[/tex]

[tex]8a_0 + 6a_1= -100[/tex]    (2)

With these equations is enough to solve the system

[tex]a_0 + 7a_1=-50[/tex]    (1)

[tex]8a_0 + 6a_1= -100[/tex]    (2)

Multiply the equation (1) by -8 and add it to the equation (2)

[tex]-8a_0 - 56a_1=400[/tex]    (1)

[tex]8a_0 + 6a_1= -100[/tex]    (2)

-----------------------------------------------------

[tex]-50a_1 = 300\\\\a_1 = -6[/tex]

Then

[tex]a_0 + 7(-6) = -50\\\\a_0 = -50+42\\\\a_0=-8[/tex]

Finally the equation is:

[tex]x^2 +y^2 -8x - 6y = 0[/tex]

ACCESS MORE